Health Economic Evaluation in Healthcare Management : A Systematic Review of Cost-Effectiveness Studies in Hospital Operations - Nuriyah Nuriyah; Muhammad Akbar; Reza Fahrepi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Healthcare systems worldwide face increasing financial constraints while maintaining quality care standards. In this context, health economic evaluation has become a crucial tool for informing evidence-based resource allocation decisions within hospital operations. This systematic review aims to synthesize current evidence on cost-effectiveness studies in hospital operations and to identify the key factors that contribute to efficient healthcare management. A comprehensive search was conducted across PubMed, Scopus, and Web of Science databases for articles published between 2020 and 2024. The keywords applied included “cost-effectiveness,” “health economic evaluation,” “hospital operations,” and “healthcare management.” Studies were screened following PRISMA guidelines, and a total of twenty-five peer-reviewed articles met the inclusion criteria, representing diverse healthcare settings, interventions, and geographical contexts. The review identified several key themes, including the adoption of digital health interventions, the implementation of quality improvement collaboratives, and the integration of performance evaluation indicators in hospital management systems. Cost-effectiveness ratios varied significantly across interventions, with digital health solutions—such as telemedicine, electronic health records, and predictive analytics—showing particularly promising results in terms of both cost savings and patient outcomes. Overall, the findings confirm that health economic evaluation is essential for optimizing hospital operations. Future research should prioritize the standardization of evaluation methods, the inclusion of broader outcome measures, and the development of comprehensive frameworks that integrate both clinical and economic perspectives in healthcare management.